Performance of nearly fixed offset asymmetric channel‐cut crystals for X‐ray monochromators. (16th October 2019) - Frahm, Ronald; Diao, Qianshun; Murzin, Vadim; Bornmann, Benjamin; Lützenkirchen-Hecht, Dirk; Hong, Zhen; Li, Tang
Abstract : A novel, asymmetrically cut, channel‐cut crystal was designed and manufactured with the aim to significantly reduce the beam offset change during energy scans. The improvement was verified with synchrotron radiation from an undulator source. The importance of even small, generally so far neglected, asymmetries is pointed out for high‐accuracy monochromators. Abstract : X‐ray double‐crystal monochromators face a shift of the exit beam when the Bragg angle and thus the transmitted photon energy changes. This can be compensated for by moving one or both crystals accordingly. In the case of monolithic channel‐cut crystals, which exhibit utmost stability, the shift of the monochromated beam is inevitable. Here we report performance tests of novel, asymmetrically cut, channel‐cut crystals which reduce the beam movements by more than a factor of 20 relative to the symmetric case over the typical energy range of an EXAFS spectrum at the Cu K ‐edge. In addition, the presented formulas for the beam offset including the asymmetry angle directly indicate the importance of this value, which has been commonly neglected so far in the operation of double‐crystal monochromators.